‘I was not to forget that my reader comes from another world’: An Academic Literacies Perspective on Shuttling Between the Workplace and the Academy - Ndlangamandla, Sibusiso C. (Critical Studies in Teaching and Learning, 2023)
In response to pressure to participate in the ‘knowledge economy’, universities are offering a wide range of different masters programmes oriented to the professions. Universities are opening their doors without fully understanding what these programmes entail, and with little attention to the literacy challenges that students face together with supervisors and academic literacy teachers. This article contributes to our understanding of the mixed forms of academic discourse produced by postgraduates in professional masters’ programmes by focusing on students registered for the MTech in Policing at a large ODL (Open Distance Learning) university at the point where they are writing research proposals. I trace how students use recontextualisation strategies, such as mimicry and transformation, to signal how they engage with research literacies, as they shuttle between the workplace and academic contexts. The implications for supervisors and literacy educators about the nature of social practices in an ODL context acknowledge and embrace hybridity as an emerging feature of the research literacy practices, rather than as a problem to be erased, based on a proposed hybrid PWU (Profession Workplace University) model.